2019
DOI: 10.1002/ijc.32355
|View full text |Cite
|
Sign up to set email alerts
|

CARD9 prevents lung cancer development by suppressing the expansion of myeloid‐derived suppressor cells and IDO production

Abstract: Caspase recruitment domain‐containing protein 9 (CARD9) is an adaptor protein and highly expressed in myeloid cells. Our previous study demonstrates a critical protective effect of CARD9 in the development of colitis‐associated colon cancer. Nevertheless, the effect of CARD9 in lung cancer remains unclear. Here, using a mouse Lewis lung cancer model, we found the tumor burden of CARD9−/− mice was much heavier than that in wild‐type (WT) mice. More myeloid‐derived suppressor cells (MDSCs) were accumulated and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 34 publications
(94 reference statements)
1
31
2
Order By: Relevance
“…Aberrant activation of CARD9 usually causes a series of inflammatory diseases or cancers. Qu et al demonstrated the critical role of CARD9 in the development of LC for the first time [38] and draw a conclusion that CARD9 prevented lung cancer development by suppressing the accumulation of immunosuppressive cells MDSCs and its downstream product IDO production. Moreover, correlations between CARD9 expressions and MDSCs relative genes were further confirmed in tumor tissues from…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant activation of CARD9 usually causes a series of inflammatory diseases or cancers. Qu et al demonstrated the critical role of CARD9 in the development of LC for the first time [38] and draw a conclusion that CARD9 prevented lung cancer development by suppressing the accumulation of immunosuppressive cells MDSCs and its downstream product IDO production. Moreover, correlations between CARD9 expressions and MDSCs relative genes were further confirmed in tumor tissues from…”
Section: Discussionmentioning
confidence: 99%
“…Further studies suggested that knocking down CARD9 expression enhanced the expression of IDO in MDSCs through the noncanonical NF-κB pathway, which manifested as increased expression of NIK, p-P100, p52, and RelB. Thus, the CARD9-NF-κB-IDO pathway in MDSCs can inhibit the suppressive function of MDSCs and prevent LC development [62].…”
Section: Caspase Recruitment Domain-containing Proteinmentioning
confidence: 99%
“…In our opinion, for one thing, the expression of CARD9 varied in different NSCLC cells, a suggestion of important role of CARD9 within NSCLC cells for tumor development. For another, it is typical of tumor to accumulate myeloid cells [10], such as macrophages [12,20], which should lead to increased CARD9 in vivo. We surmised that dramatical downregulation of CARD9 in NSCLC cells contributed to the decreased CARD9 in vivo, which may play a role in NSCLC development.…”
Section: E C T O R C a R D 9 S H C O N T R O L S H C A R Dmentioning
confidence: 99%
“…Our previous research on the difference of protein profiles of the benign and malignant pleural effusion by proteomics technology found that CARD9 was decreased in malignant pleural effusion, and the mechanism was not clear [9]. In the latest study of CARD9 in lung cancer, Qu et al [10] reported that CARD9 suppressed lung cancer development by inhibiting the expansion of myeloid-derived suppressor cells (MDSCs) and indoleamine 2,3-dioxygenase (IDO) production.…”
Section: Introductionmentioning
confidence: 99%